Stationary phase for chromatography
By developing a stationary phase made of polymers with hydrophilic groups in the inorganic carrier particles, the problem of insufficient separation characteristics of hydrophilic compounds in the prior art is solved, and efficient separation of hydrophilic substances is achieved.
Patent Information
- Application Number
- CN202311359922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-08-30
- Filing Date
- 2019-08-30
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing chromatography technology, the separation characteristics of the fixed relatively hydrophilic compounds are insufficient, making it difficult to effectively separate hydrophilic substances.
A stationary phase for chromatography composed of inorganic carrier particles is developed, which improves its molecular recognition ability by bonding polymers with hydrophilic groups and manufacturing through specific processes.
Good separation characteristics of hydrophilic substances are achieved, and the separation efficiency and effect of chromatography are improved.
Smart Images

Figure BDA0004505852390000031 
Figure BDA0004505852390000051 
Figure BDA0004505852390000101
Abstract
Description
[0001] This application is a divisional application of the Chinese invention patent application (PCT application number PCT / JP 2019 / 034204) with an application date of August 30, 2019, application number 201980056782.1, and invention name “Stationary Phase for Chromatography”. Technical Field
[0002] The present invention relates to chromatography technology and more particularly to a stationary phase used in chromatography. Background Art
[0003] As chromatography, liquid chromatography and supercritical fluid chromatography (SFC) are well known.
[0004] As the stationary phase used in SFC, for example, as described in Non-Patent Document 1, there can be cited silica gel or a stationary phase obtained by modifying its surface with various atomic groups. In particular, the stationary phase often used in SFC is a substance bonded with a (2-pyridyl)ethyl group called 2-ethylpyridine. Even when a basic compound that has a wide range of peaks due to tailing in an ordinary stationary phase is separated, it will become a sharp peak and dissolve when using this stationary phase, and the acidic compound can also be appropriately retained, so it is preferably used.
[0005] However, as pointed out in Non-Patent Document 2, there are many stationary phases that have similar retention tendencies for various compounds and have no characteristic differences.
[0006] Most of the materials used as stationary phases for SFC so far are silica gel or materials whose surfaces are modified with various low molecular weight compounds. On the other hand, there are also reports of stationary phases obtained by modifying the surface of silica gel with polymers.
[0007] For example, there are examples of using vinyl polymers as stationary phases for high performance liquid chromatography, as described in Non-Patent Document 3 and Patent Document 1. In these examples, it is known that poly(4-vinylpyridine) chemically bonded to the surface of silica gel is used and is effective for separation of various compounds.
[0008] In order to separate hydrophilic substances such as bio-related substances, there is also known a technique in which a zwitterionic substance supported on a monolithic carrier is used and applied to liquid chromatography (Patent Document 2).
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2003-337125
[0012] Patent Document 2: Japanese Patent Application Publication No. 2010-190602
[0013] Non-patent literature
[0014] Non-patent document 1: C. West et al., J. Chromatogr. A, 1203 (2008) 105
[0015] Non-patent document 2: C. West et al., J. Chemometrics, 26 (2012) 52
[0016] Non-patent document 3: H. Ihara et al., J. Liq. Chromatogr. Relat. Technol. 26 (2003) 2491 Summary of the invention
[0017] Problems to be solved by the invention
[0018] An object of the present invention is to provide a stationary phase for chromatography having excellent molecular recognition ability, in particular, excellent separation characteristics for hydrophilic compounds.
[0019] Means for solving problems
[0020] The inventors of the present application have repeatedly conducted in-depth studies to solve the above-mentioned problems, and as a result, have found that the following chromatographic stationary phase exhibits good molecular recognition ability in chromatography, especially supercritical fluid chromatography. The chromatographic stationary phase is composed of inorganic carrier particles, and the inorganic carrier particles are bonded with a polymer having a hydrophilic group in the repeating units of the main chain, and the chromatographic stationary phase is obtained by a manufacturing method including specific steps, thereby completing the present invention.
[0021] That is, the present invention is as follows.
[0022] [1] A stationary phase for chromatography, comprising inorganic carrier particles to which a polymer having a hydrophilic group in a repeating unit of the main chain is bonded,
[0023] The stationary phase is produced by a production method comprising any of the following steps (i) to (v).
[0024] The manufacturing method comprises:
[0025] (i) a step of subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to free radical copolymerization with inorganic carrier particles to which a polymerizable functional group is bonded;
[0026] (ii) a step of subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to free radical polymerization in the presence of a chain transfer agent having a crosslinkable silyl group at the end to obtain a polymer, and a step of subjecting the obtained polymer to silane coupling on the surface of inorganic carrier particles;
[0027] (iii) a step of copolymerizing a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group with a silane coupling agent having a polymerizable double bond, and a step of silane coupling the obtained polymer on the surface of inorganic carrier particles;
[0028] (iv) a step of copolymerizing a silane coupling agent having a polymerizable double bond and a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group in the presence of inorganic carrier particles;
[0029] (v) A step of introducing a chain transfer functional group onto the surface of the inorganic carrier particles and subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to radical polymerization.
[0030] [2] The stationary phase for chromatography according to [1], wherein the (meth)acrylic monomer having a hydrophilic group or the (meth)acrylamide monomer having a hydrophilic group has a structure represented by the following formula (1).
[0031] [Chemical formula 1]
[0032]
[0033] In formula (1),
[0034] R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms,
[0035] R 2 is a single bond or an alkylene group having 1 to 12 carbon atoms,
[0036] R 3 is a single bond or an alkylene group having 1 to 6 carbon atoms,
[0037] X 2 is -O-, -NH- or -N(CH3)-,
[0038] Y 2 For a single key, -N + H2-、-N + (R 4 )2-or a is an integer of 1 to 5, b is an integer of 1 to 20,
[0039] Z 2 is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, -N + R 4 3. -CO2- or R 4 It is hydrogen, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms.
[0040] [3] The chromatographic stationary phase according to [1] or [2], wherein the inorganic carrier particles are porous inorganic particles or non-porous inorganic particles.
[0041] [4] The chromatographic stationary phase according to [3], wherein the inorganic carrier particles are porous inorganic particles, and the porous inorganic particles are core-shell type particles.
[0042] [5] The chromatographic stationary phase according to any one of [1] to [4], wherein the average particle size is 0.1 μm to 50 μm.
[0043] [6] The chromatographic stationary phase according to any one of [1] to [5], which is used for supercritical fluid chromatography.
[0044] [7] A method for separating a target substance, comprising the step of separating the target substance using the stationary phase according to any one of [1] to [6] and a mobile phase containing a supercritical fluid.
[0045] [8] A method for producing a stationary phase for chromatography, comprising any of the following steps (i) to (v).
[0046] The manufacturing method comprises:
[0047] (i) a step of subjecting a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group to free radical copolymerization with inorganic carrier particles to which a polymerizable functional group is bonded;
[0048] (ii) a step of subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to free radical polymerization in the presence of a chain transfer agent having a crosslinkable silyl group at the end to obtain a polymer, and a step of subjecting the obtained polymer to silane coupling on the surface of inorganic carrier particles;
[0049] (iii) a step of copolymerizing a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group with a silane coupling agent having a polymerizable double bond, and a step of silane coupling the obtained polymer on the surface of inorganic carrier particles;
[0050] (iv) a step of copolymerizing a silane coupling agent having a polymerizable double bond and a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group in the presence of inorganic carrier particles;
[0051] (v) A step of introducing a chain transfer functional group onto the surface of the inorganic carrier particles and subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to radical polymerization.
[0052] [9] The method for producing a chromatographic stationary phase according to [8], wherein the (meth)acrylic monomer having a hydrophilic group or the (meth)acrylamide monomer having a hydrophilic group has a structure represented by the following formula (1).
[0053] [Chemical formula 2]
[0054]
[0055] In formula (1),
[0056] R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms,
[0057] R 2 is a single bond or an alkylene group having 1 to 12 carbon atoms,
[0058] R 3 is a single bond or an alkylene group having 1 to 6 carbon atoms,
[0059] X 2 is -O-, -NH- or -N(CH3)-,
[0060] Y 2 For a single key, -N + H2-、-N + (R 4 )2-or a is an integer of 1 to 5, b is an integer of 1 to 20,
[0061] Z 2 is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, -N + R 4 3. -CO2 - or R 4 It is hydrogen, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms.
[0062]
[10] The method for producing a chromatographic stationary phase according to [8] or [9], wherein the inorganic carrier particles are porous inorganic particles or non-porous inorganic particles.
[0063]
[11] The method for producing a chromatographic stationary phase according to
[10] , wherein the inorganic carrier particles are porous inorganic particles, and the porous inorganic particles are core-shell type particles.
[0064] Effects of the Invention
[0065] According to the present invention, a chromatographic stationary phase having excellent molecular recognition ability, particularly excellent separation characteristics for hydrophilic substances, can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] [ Figure 1 ] is a chromatogram showing the separation of water-soluble vitamins using SFC, wherein poly (PA) bonded silica gel is used as the stationary phase.
[0067] [ Figure 2 ] is a chromatogram showing the separation of water-soluble vitamins using SFC, wherein poly (4-vinylpyridine) bonded silica gel is used as the stationary phase.
[0068] [ Figure 3 ] is a chromatogram showing the separation of uridine by HPLC, in which various vinyl polymer-bonded silica gels are used as the stationary phase.
[0069] [ Figure 4 ] is a chromatogram showing the separation of uridine by HPLC, in which existing commercially available silica gel is used as the stationary phase.
[0070] [ Figure 5 ] is a chromatogram showing the separation of uridine by HPLC, wherein poly(PA) bonded silica gel prepared using 1.6 μm silica gel as a raw material is used as a stationary phase.
[0071] [ Figure 6 ] is a chromatogram showing the separation of uridine by HPLC, wherein poly(PA) bonded silica gel prepared by various preparation methods and using core-shell silica gel as a raw material is used as a stationary phase. DETAILED DESCRIPTION
[0072] The chromatographic stationary phase of the present invention comprises inorganic support particles to which a polymer having a hydrophilic group in a repeating unit of a main chain is bonded.
[0073] It should be noted that the stationary phase in the present invention refers to a material that is fixed inside an analytical tool (column or capillary) in chromatography and causes separation by distributing the separation object between it and a fluid that moves while in contact with it. When it is a particle, it sometimes refers to an aggregate formed by filling the particles, and sometimes refers to its individual particles.
[0074] Here, the "hydrophilic group" preferably includes, for example, zwitterion, cation or anion ionic groups, and also includes hydroxyl group, carboxyl group, sulfonic acid group, amide group, amino group, dialkylamino group, trialkylamino salt group, trialkylphosphonium salt group and polyoxyethylene group.
[0075] In the stationary phase according to one embodiment of the present invention, a chemical bond (covalent bond) is formed between the carrier and the polymer from the viewpoint of stability and separation performance. Specifically, a production method including any of the steps shown in the following (i) to (v) can be exemplified.
[0076] In the stationary phase for chromatography, the polymer can be coated by utilizing physical bonding with a support. However, in this case, the polymer may be eluted by the solvent, so this is not considered to be a preferred method.
[0077] The manufacturing method comprises:
[0078] (i) a step of subjecting a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group to free radical copolymerization with inorganic carrier particles to which a polymerizable functional group is bonded;
[0079] (ii) a step of subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to free radical polymerization in the presence of a chain transfer agent having a crosslinkable silyl group at the end to obtain a polymer, and a step of subjecting the obtained polymer to silane coupling on the surface of inorganic carrier particles;
[0080] (iii) a step of copolymerizing a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group with a silane coupling agent having a polymerizable double bond, and a step of silane coupling the obtained polymer on the surface of inorganic carrier particles;
[0081] (iv) a step of copolymerizing a silane coupling agent having a polymerizable double bond and a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group in the presence of inorganic carrier particles;
[0082] (v) A step of introducing a chain transfer functional group onto the surface of the inorganic carrier particles and subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to radical polymerization.
[0083] In any method, the stereoregularity of the produced polymer can be controlled by the polymerization temperature, polymerization solvent, additives, etc. during polymerization.
[0084] The production method including the step (i) will be described.
[0085] The inorganic carrier particles to which the polymerizable functional group is bonded (hereinafter, also simply referred to as carrier) used in the production method including the step (i) can be produced by the following method.
[0086] Examples of the polymerizable functional group bonded to the carrier include radical polymerizable functional groups, such as vinyl, allyl, isopropenyl, or alkenyl having 4 to 12 carbon atoms and a double bond at the ω position. Among them, vinyl, allyl, or isopropenyl is preferred.
[0087] In addition, as inorganic carrier particles, porous inorganic particles or non-porous inorganic particles are used. Suitable carriers for porous inorganic particles are silica gel, alumina, zirconium oxide, titanium dioxide, magnesium oxide, glass, kaolin, titanium oxide, silicate, hydroxyapatite, etc. Preferred porous inorganic particles are silica gel, alumina or glass.
[0088] Examples of suitable supports for the nonporous inorganic particles include nonporous silica gel and nonporous titanium oxide.
[0089] When porous silica gel or non-porous silica gel (hereinafter, sometimes simply described as "silica gel" as a concept including both) is used as the carrier, the polymerizable functional group is chemically bonded to the carrier via the silanol group of each silica gel.
[0090] When using a carrier other than porous silica gel or non-porous silica gel, by performing surface treatment on the carrier, it is possible to suppress the excessive adsorption of the separation target substance to the carrier itself, and to bond with the polymerizable functional group via the group introduced by the surface treatment. Examples of the surface treatment agent include silane coupling agents such as aminopropylsilane and titanate-based / aluminate-based coupling agents.
[0091] When porous silica gel is used as the carrier, it may be a core-shell type silica gel called core-shell or peripheral, in which the core is non-porous and only the surface layer is porous.
[0092] When a core-shell type carrier (also referred to as core-shell particle) is used, the carrier described later can be used.
[0093] The support to which the polymerizable functional group is bonded as described above can be obtained, for example, by silane coupling a compound represented by the following formula (I) and a support (preferably silica gel).
[0094] [Chemical formula 3]
[0095] WXY-SiR 3-n Z n (I)
[0096] (In formula (I), W is a vinyl group, an allyl group, an isopropenyl group, or an alkenyl group having 4 to 12 carbon atoms and having a double bond at the ω position; X is an amide group, an ester group, an N-alkylamide group having 1 to 3 carbon atoms, an ether group, a sulfoxide group, a sulfone group, a thioether group, or a phosphate group; Y is an alkylene group having 1 to 30 carbon atoms; R is independently an alkyl group having 1 to 3 carbon atoms; and Z is a leaving group capable of forming a bond between the silicon atom in formula (I) and the carrier. n is an integer of 1 to 3.)
[0097] In the above formula (I), W is preferably a vinyl group, an allyl group or an isopropenyl group.
[0098] In the above formula (I), X is a part of the linking group between W and the terminal Z group, and is preferably an amide group, an N-alkylamide group having 1 to 3 carbon atoms, or an ester group.
[0099] Y in the above formula (I) is preferably an alkylene group having 1 to 5 carbon atoms, and more preferably any one of a methylene group, an ethylene group, and a propylene group (trimethylene group).
[0100] In the above formula (I), R is preferably a methyl group or an ethyl group.
[0101] Z in the above formula (I) is a leaving group, and any atomic group may be used as long as it is a group that can form a bond between the silicon atom in the formula (I) and an atom such as oxygen constituting the carrier. In order to achieve a good balance between ease of handling and reactivity, commonly used groups include alkoxy groups having 1 to 5 carbon atoms, particularly preferably methoxy or ethoxy, and halogen (chlorine, bromine or iodine), alkyl mercapto groups having 1 to 20 carbon atoms (alkyl mercaptyl), dimethylamino, diethylamino, pyrrolidinyl, nitrogen-containing groups such as imidazolyl, allyl or 2-methyl-2-propenyl. The reaction conditions (including the addition of a catalyst) may be adjusted according to the type of leaving group.
[0102] The compound represented by the above formula (I) can be prepared by reacting a compound having a structure represented by W of the above formula (I) with -Y-SiR 3-n Z nThe compound having the structure of is obtained by reacting.
[0103] The reaction of these compounds produces "-X-" of the above-mentioned formula (I).
[0104] Examples of the compound having a structure represented by W include acrylic acid in which hydrogen atoms bonded to carbon atoms of vinyl groups may be substituted with alkyl groups having 1 to 12 carbon atoms, and halides of acrylic acid in which hydrogen atoms bonded to carbon atoms of vinyl groups may be substituted with alkyl groups having 1 to 12 carbon atoms.
[0105] As -Y-SiR having the above formula (I) 3-n Z n Examples of the compound having a structure of include a silane coupling agent having the group as a precursor of X described above and having an alkoxy group having 1 to 5 carbon atoms as a leaving group.
[0106] The support to which the polymerizable functional group is bonded used in the present invention is preferably a surface-modified silica gel obtained by silane coupling the compound represented by the above formula (I) and silica gel.
[0107] When produced using the production method including the step (i) described above, the stationary phase involved in one embodiment of the present invention is a stationary phase obtained by copolymerizing a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group and a carrier to which a polymerizable functional group is bonded.
[0108] As a method of copolymerization, there can be mentioned a method of copolymerizing both the (meth)acryloyl group and the polymerizable functional group of the above-mentioned monomer, and a known method can be used for the reaction conditions in this case.
[0109] Examples of the (meth)acrylic monomer having a hydrophilic group or the (meth)acrylamide monomer having a hydrophilic group include monomers represented by the following formula (1).
[0110] [Chemical formula 4]
[0111]
[0112] In formula (1),
[0113] R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms,
[0114] R 2 is a single bond or an alkylene group having 1 to 12 carbon atoms,
[0115] R 3 is a single bond or an alkylene group having 1 to 6 carbon atoms,
[0116] X2 is -O-, -NH- or -N(CH3)-,
[0117] Y 2 For a single key, -N + H2-、-N + (R 4 )2-or a is an integer of 1 to 5, b is an integer of 1 to 20,
[0118] Z 2 is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, -N + R 4 3. -CO2 - or R 4 It is hydrogen, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms.
[0119] [Chemical formula 5]
[0120] In formula (1), X 2 is -O- and Y 2 for When the monomer is a monomer represented by the following formula (2), preferably, the monomer is a monomer represented by the following formula (2).
[0121]
[0122] In formula (2), R 1 is hydrogen or methyl, R 2 is methylene, ethylene, propylene, butylene, pentylene or hexylene, preferably methylene or ethylene, R 3 is methylene, ethylene, propylene, butylene, pentylene or hexylene, preferably methylene or ethylene, R 4 It is methyl or ethyl, preferably methyl.
[0123] Specific examples of the monomer represented by the formula (2) include 2-((meth)acryloyloxy)ethyl-2'-(trimethylammonio)ethyl phosphate, 3-((meth)acryloyloxy)propyl-2'-(trimethylammonio)ethyl phosphate, 4-((meth)acryloyloxy)butyl-2'-(trimethylammonio)ethyl phosphate, 5-((meth)acryloyloxy)pentyl-2'-(trimethylammonio)ethyl phosphate, 6-((meth)acryloyloxy)hexyl-2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(triethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(triethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(trimethyl ... '-(tripropylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(tributylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(tricyclohexylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(triphenylammonio)ethyl phosphate, 2-((meth)acryloyloxy)propyl-2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)butyl-2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)pentyl-2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)hexyl-2'-(trimethylammonio)ethyl phosphate, and the like. Among the above, 2-((meth)acryloyloxy)ethyl-2′-(trimethylammonio)ethyl phosphate (2-methacryloyloxyethyl phosphorylcholine: hereinafter sometimes abbreviated to “PA”) is preferably used in view of easy availability.
[0124] In formula (1), X 2 is -O-, -NH- or -N(CH3)-, and Y 2 -N + (R 4 )2-, preferably, a monomer represented by the following formula (3) is used.
[0125] [Chemical formula 6]
[0126]
[0127] In formula (3), R 1 is hydrogen or methyl, R 2 is an alkylene group having 1 to 12 carbon atoms, R 4 is hydrogen, methyl or ethyl, Z 2 For R 4 The same group. - It is a fluoride, chloride, bromide or iodide.
[0128] Specific examples of the monomer represented by the formula (3) include methacryloylaminomethyltrimethylammonium chloride, 2-(methacryloylamino)ethyltrimethylammonium chloride, 3-(methacryloylamino)propyltrimethylammonium chloride, 4-(methacryloylamino)butyltrimethylammonium chloride, 5-(methacryloylamino)pentyltrimethylammonium chloride, 6-(methacryloylamino)hexyltrimethylammonium chloride, methacryloylaminomethyltrimethylammonium bromide, 2-(methacryloylamino)ethyltrimethylammonium bromide, 3-(methacryloylamino)propyltrimethylammonium chloride, 4-(methacryloylamino)butyltrimethylammonium chloride, 5-(methacryloylamino)pentyltrimethylammonium chloride, 6-(methacryloylamino)hexyltrimethylammonium chloride ...3-(methacryloylamino)propyltrimethylammonium chloride, 3-(methacryloylamino)butyltrimethylammonium chloride, 3-(methacryloylamino)propyltrimethylammonium chloride, 3-(methacryloylamino)butyltrimethylammonium chloride, 3-(methacryloylamino)propyltrimethylammonium chloride, 3-(methacryloylamino)butyltrimethylammonium chloride, 3-(methacryloylamino)propyltrimethylammonium chloride, 3-(methacryloylamino)butyltrimethylammonium chloride, 3-(methacryloylamino)propyltrimethylam -(Methacryloylamino)propyltrimethylammonium bromide, 4-(Methacryloylamino)butyltrimethylammonium bromide, 5-(Methacryloylamino)pentyltrimethylammonium bromide, 6-(Methacryloylamino)hexyltrimethylammonium bromide, methacryloylaminomethyltrimethylammonium iodide, 2-(Methacryloylamino)ethyltrimethylammonium iodide, 3-(Methacryloylamino)propyltrimethylammonium iodide, 4-(Methacryloylamino)butyltrimethylammonium iodide, 5-(Methacryloylamino)pentyltrimethylammonium iodide, 6-(Methacryloylamino)hexyltrimethylammonium iodide, methacryloyloxymethyltrimethylammonium chloride, 2-(methacryloyloxy)ethyltrimethylammonium chloride, 3-(methacryloyloxy)propyltrimethylammonium chloride, 4-(methacryloyloxy)butyltrimethylammonium chloride, 5-(methacryloyloxy)pentyltrimethylammonium chloride, 6-(methacryloyloxy)hexyltrimethylammonium chloride, methacryloyloxymethyltrimethylammonium bromide, 2-(methacryloyloxy)ethyltrimethylammonium bromide, 3-(methacryloyloxy) Propyltrimethylammonium bromide, 4-(methacryloyloxy)butyltrimethylammonium bromide, 5-(methacryloyloxy)pentyltrimethylammonium bromide, 6-(methacryloyloxy)hexyltrimethylammonium bromide, methacryloyloxymethyltrimethylammonium iodide, 2-(methacryloyloxy)ethyltrimethylammonium iodide, 3-(methacryloyloxy)propyltrimethylammonium iodide, 4-(methacryloyloxy)butyltrimethylammonium iodide, 5-(methacryloyloxy)pentyltrimethylammonium iodide, 6-(methacryloyloxy)hexyltrimethylammonium iodide.
[0129] In formula (1), Y 2 -N + (R 4 )2-, preferably, a monomer represented by the following formula (4) is used.
[0130] [Chemical formula 7]
[0131]
[0132] In formula (4), X 2 is -O-, -NH- or -N(CH3)-, R 1 is hydrogen or methyl, R2 is an alkylene group having 1 to 12 carbon atoms, R 3 is an alkyl group having 1 to 12 carbon atoms, Z 2 for -CO2 - or R 4 It is hydrogen, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms.
[0133] Specific examples of the monomer represented by the above formula (4) include 2-(N-3-sulfopropyl-N,N-dimethylammonium)ethyl methacrylate, 2-(N-3-sulfopropyl-N,N-dimethylammonium)ethyl methacrylamide, 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate, and 3-[[2-(methacrylamide)ethyl]dimethylammonium]propionate.
[0134] [Chemical formula 8]
[0135] In formula (1), Y2 is When the monomer is a monomer represented by the following formula (5), preferably, the monomer is a monomer represented by the following formula (5).
[0136]
[0137] In formula (5), preferably: X 2 is -O-, -NH- or -N(CH3)-, R 1 is hydrogen or methyl, a is an integer from 1 to 5, b is an integer from 1 to 20, Z 2 is hydrogen, methyl or ethyl.
[0138] Specific examples of the monomer represented by the formula (5) include 2-hydroxyethyl methacrylate, diethylene glycol monomethacrylate, diethylene glycol monomethyl ether methacrylate, diethylene glycol monoethyl ether methacrylate, triethylene glycol monomethacrylate, triethylene glycol monomethyl ether methacrylate, triethylene glycol monoethyl ether methacrylate, tetraethylene glycol monomethacrylate, tetraethylene glycol monomethyl ether methacrylate, tetraethylene glycol monoethyl ether methacrylate, polyethylene glycol monomethacrylate, Ester, polyethylene glycol monomethyl ether methacrylate, polyethylene glycol monoethyl ether methacrylate, 2-hydroxyethyl methacrylamide, diethylene glycol monomethyl ether methacrylamide, diethylene glycol monoethyl ether methacrylamide, triethylene glycol monomethyl ether methacrylamide, triethylene glycol monoethyl ether methacrylamide, tetraethylene glycol monomethyl ether methacrylamide, tetraethylene glycol monoethyl ether methacrylamide, polyethylene glycol monomethyl ether methacrylamide, polyethylene ... Diol monomethacrylamide, polyethylene glycol monomethyl ether methacrylamide, polyethylene glycol monoethyl ether methacrylamide, 2-hydroxyethyl acrylate, diethylene glycol monoacrylate, diethylene glycol monomethyl ether acrylate, diethylene glycol monoethyl ether acrylate, triethylene glycol monoacrylate, triethylene glycol monomethyl ether acrylate, triethylene glycol monoethyl ether acrylate, tetraethylene glycol monoacrylate, tetraethylene glycol monomethyl ether acrylate, tetraethylene glycol monoethyl ether acrylate, polyethylene glycol monoacrylate, polyethylene glycol mono Methyl ether acrylate, polyethylene glycol monoethyl ether acrylate, 2-hydroxyethyl acrylamide, diethylene glycol monoacrylamide, diethylene glycol monomethyl ether acrylamide, diethylene glycol monoethyl ether acrylamide, triethylene glycol monoacrylamide, triethylene glycol monomethyl ether acrylamide, triethylene glycol monoethyl ether acrylamide, tetraethylene glycol monoacrylamide, tetraethylene glycol monomethyl ether acrylamide, tetraethylene glycol monoethyl ether acrylamide, polyethylene glycol monoacrylamide, polyethylene glycol monomethyl ether acrylamide, polyethylene glycol monoethyl ether acrylamide.
[0139] [Chemical formula 9]
[0140] In formula (1), Z 2 for When the monomer is preferably a monomer represented by the following formula (6).
[0141] [Chemical formula 10]
[0142]
[0143] In formula (6), X 2 is -O-, -NH- or -N(CH3)-, R 1 is hydrogen or methyl, R 2 is an alkylene group having 1 to 12 carbon atoms, Y 2 is a single bond, R 3is an alkyl group having 1 to 12 carbon atoms, Z 2 for -CO2 - or R 4 is hydrogen, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms; A is an element serving as a counter ion, and is lithium, sodium, potassium or cesium.
[0144] Specific examples of the monomer represented by the formula (6) include lithium 3-(methacryloyloxy)propane sulfonate, sodium 3-(methacryloyloxy)propane sulfonate, potassium 3-(methacryloyloxy)propane sulfonate, cesium 3-(methacryloyloxy)propane sulfonate, lithium 3-(methacrylamide)propane sulfonate, sodium 3-(methacrylamide)propane sulfonate, potassium 3-(methacrylamide)propane sulfonate, cesium 3-(methacrylamide)propane sulfonate, lithium 3-(N-methylmethacrylamide)propane sulfonate, sodium 3-(N-methylmethacrylamide)propane sulfonate, and sodium 3-(N-methylmethacrylamide)propane sulfonate. 3-(acryloxy)propane sulfonate, sodium 3-(acryloxy)propane sulfonate, potassium 3-(acryloxy)propane sulfonate, cesium 3-(acryloxy)propane sulfonate, lithium 3-(acryloxy)propane sulfonate, sodium 3-(acryloxy)propane sulfonate, potassium 3-(acryloxy)propane sulfonate, cesium 3-(acrylamide)propane sulfonate, lithium 3-(acrylamide)propane sulfonate, sodium 3-(acrylamide)propane sulfonate, potassium 3-(acrylamide)propane sulfonate, cesium 3-(acrylamide)propane sulfonate, lithium 3-(N-methylacrylamide)propane sulfonate, sodium 3-(N-methylacrylamide)propane sulfonate, potassium 3-(N-methylacrylamide)propane sulfonate, 2-(methacryloxy)ethanesulfonate, cesium 2-(methacryloxy)ethanesulfonate, lithium 2-(methacryloxy)ethanesulfonate, sodium 2-(methacryloxy)ethanesulfonate, potassium ...N-methylmethacrylamide)ethanesulfonate, sodium 2-(N-methylmethacrylamide)ethanesulfonate, potassium 2-(N-methylmethacrylamide)ethanesulfonate, Cesium (N-methylmethylacrylamide)ethanesulfonate, lithium 2-(acryloxy)ethanesulfonate, sodium 2-(acryloxy)ethanesulfonate, potassium 2-(acryloxy)ethanesulfonate, cesium 2-(acryloxy)ethanesulfonate, lithium 2-(acrylamide)ethanesulfonate, sodium 2-(acrylamide)ethanesulfonate, potassium 2-(acrylamide)ethanesulfonate, cesium 2-(acrylamide)ethanesulfonate, lithium 2-(acrylamide)ethanesulfonate, sodium 2-(acrylamide)ethanesulfonate, potassium 2-(acrylamide)ethanesulfonate, cesium 2-(acrylamide)ethanesulfonate, lithium 2-(N-methylacrylamide)ethanesulfonate, sodium 2-(N-methylacrylamide)ethanesulfonate, potassium 2-(N-methylacrylamide)ethanesulfonate, cesium 2-(N-methylacrylamide)ethanesulfonate.
[0145] In formula (1), R 2 and R 3 is a single bond, and X 2 In the case of -NH-, preferably, a monomer represented by the following formula (7) is used.
[0146] [Chemical formula 11]
[0147]
[0148] In formula (7), R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms, Z 2 It is hydrogen or an alkyl group having 1 to 6 carbon atoms.
[0149] Specific examples of the monomer represented by the formula (7) include acrylamide, methacrylamide, N-methylacrylamide, N-methylmethacrylamide, N-ethylacrylamide, and N-ethylmethacrylamide.
[0150] As the copolymerization conditions, free radical copolymerization can be cited, and a small amount of free radical generator can be used as a catalyst to cause copolymerization. The free radical generator can use a known free radical generator used in polymerization reactions, and specific examples thereof include azo compounds and peroxides. It can be inferred that the stationary phase involved in one embodiment of the present invention obtained by using the raw materials described above and the production method including step (i) has the following structure.
[0151] [Chemical formula 12]
[0152]
[0153] (In formula II, W' and W" are each derived from W of formula (I), and are groups generated by addition polymerization; X is an amide group, an ester group, an N-alkylamide group having 1 to 3 carbon atoms, an ether group, a sulfoxide group, a sulfone group, a thioether group, or a phosphate group; Y is an alkylene group having 1 to 30 carbon atoms; V is an ether group bonded to the silica gel surface, or an unreacted Z group or R group represented by the above formula (I); X 2 , Y 2 , Z 2 , R 1 , R 2 , R 3 The same as described in the above formula (1).
[0154] In the above formula (II), specific examples of W' include a single bond and an optionally branched alkylene group having 1 to 10 carbon atoms. Preferred examples include a single bond, a methylene group, an ethylene group, and a propylene group.
[0155] In the above formula (II), specific examples of W" include hydrogen or an alkyl group having 1 to 12 carbon atoms.
[0156] Preferred groups for X and Y in formula (II) are the same groups as those in formula (I).
[0157] X in formula (II) 2 , Y 2 , Z 2 , R 1 , R 2 , R 3 The same as described in the above formula (1), X 2 With Y 2 The preferred combinations and the preferred structures resulting therefrom are the same as those described for the above formulae (2) to (7).
[0158] In the formula (II), p is 1 to 10, and q is about 10 to 3000. Preferably, p is 1 to 5, and q is preferably 15 to 2500, and more preferably 20 to 2000.
[0159] For V of formula (II), in the compound represented by the above formula (I), when n=1, V=R; when n=2, the proportion of unreacted Z groups or R groups relative to the total number of V is 50-100%; when n=3, the proportion of unreacted Z groups or R groups relative to the total number of V is 0-100%.
[0160] X in formula (II) 2 , Y 2 , Z 2 , R 1 , R 2 , R 3 As a specific example, the content described in any one of the above formulas (2) to (7) is similar to the content described in the above formula (1).
[0161] Next, a production method including step (ii) for obtaining a stationary phase according to one embodiment of the present invention will be described.
[0162] The production method including the step (ii) is a production method including the steps of conducting radical polymerization in the presence of a chain transfer agent having a crosslinkable silyl group at a terminal, and silane coupling the obtained polymer on the surface of a support.
[0163] As a chain transfer agent having a crosslinkable silyl group at the end used in the production method including step (ii), a compound represented by the following formula (III) can be exemplified. The crosslinkable silyl group in the present invention refers to a silyl group of the following formula (III) to which a leaving group represented by Z is bonded. The same applies to the compounds used in the following other production methods.
[0164] [Chemical formula 13]
[0165] R 3-n Z n Si-YT (III)
[0166] (In formula (III), R is independently an alkyl group having 1 to 5 carbon atoms, Z is a leaving group capable of forming a bond between the silicon atom in formula (III) and the carrier. Y is a single bond or an alkylene group having 1 to 30 carbon atoms, and T is a chain transfer functional group. n is an integer of 1 to 3.)
[0167] In formula (III), R is preferably a methyl group, an ethyl group or a propyl group. Z is a leaving group and may be any atomic group as long as it is a group that can form a bond between the silicon atom in formula (III) and the oxygen constituting silica gel.
[0168] In order to achieve a good balance between the ease of handling and the reactivity, the group commonly used as the leaving group is an alkoxy group having 1 to 5 carbon atoms, among which methoxy or ethoxy can be exemplified, and halogen (chlorine, bromine or iodine), dimethylamino, diethylamino, pyrrolidinyl, nitrogen-containing groups such as imidazolyl, and allyl and isopropenyl can also be used. The reaction conditions (including the addition of a catalyst) can be adjusted according to the type of the leaving group. Y is more preferably a single bond or an alkylene group having 1 to 10 carbon atoms. T is a chain transfer functional group. The chain transfer functional group refers to a functional group in which the chain transfer reaction actively occurs in the polymerization reaction accompanied by the transfer of the growth active species and the reinitiation reaction. By the presence of the chain transfer functional group, the molecular weight and terminal structure of the generated polymer can be controlled to a certain extent. Specific examples of the chain transfer functional group include preferably a halogenated alkyl group having 1 to 12 carbon atoms, an alkyl group having 1 to 12 carbon atoms having a thiol group at the terminal, or an alkyl group having 1 to 12 carbon atoms having a disulfide group in the group.
[0169] Examples of the halogen of the halogenated alkyl group having 1 to 12 carbon atoms include chlorine, bromine and iodine, and examples of the alkyl group include an alkyl group having 1 to 3 carbon atoms.
[0170] In the presence of such a chain transfer agent, a small amount of a free radical generator can be used as a catalyst to perform free radical polymerization of a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group, thereby obtaining a compound having a structure represented by the following formula (IV). At this time, the molecular weight can be controlled to a certain extent by the molar ratio of the chain transfer agent to the monomer. The free radical generator can use a known free radical generator used in a polymerization reaction, and specific examples thereof include azo compounds and peroxides. For the carrier, in addition to silica gel, the same carrier as that used in the manufacturing method including the above-mentioned step (i) can be used, and for the (meth) acrylic monomer having a hydrophilic group or the (meth) acrylamide monomer having a hydrophilic group, the same monomer as that in the manufacturing method including the step (i) can also be used. In addition, for the free radical generator, the same free radical generator as that in the manufacturing method including the step (i) can also be used.
[0171] [Chemical formula 14]
[0172]
[0173] (In formula IV, T' is derived from T in formula III and is a group generated by a chain transfer reaction, X 2 , Y 2 , Z 2 , R 1 , R 2 , R 3 The same as described in the above formula (1). q is an integer of 2 to 300.
[0174] X in formula (IV) 2 , Y 2 , Z 2 , R 1 , R 2 , R 3 As a specific example, the content described in any one of the above formulas (2) to (7) is similar to that described in the above formula (1).
[0175] In formula (IV), T' is an alkyl group having 1 to 12 carbon atoms and having a halogen bonded to the terminal, and is an alkylene residue having 1 to 12 carbon atoms substituted with the halogen; and is a sulfide group when T is an alkyl group having 1 to 12 carbon atoms and having a thiol group at the terminal or an alkyl group having 1 to 12 carbon atoms and having a disulfide group in the group.
[0176] The support used in the method for producing the stationary phase (ii) according to one embodiment of the present invention may be the same support as that used in the method for producing the stationary phase (i).
[0177] As for the method of bonding the compound represented by the formula (III) to the carrier by a silane coupling reaction, a known silane coupling method can be used.
[0178] It is estimated that the stationary phase according to one embodiment of the present invention obtained by the production method including the above step (ii) has a structure represented by the following formula (V).
[0179] [Chemical formula 15]
[0180]
[0181] (In formula (V), Y is a single bond or an alkylene group having 1 to 30 carbon atoms, V is an ether group bonded to the surface when the inorganic carrier is silica gel, or an unreacted Z group or R group represented by the above formula (III), T' is derived from T of formula III and is a group generated by a chain transfer reaction, and X 2 , Y 2 , Z 2 , R 1 , R 2 , R 3 The same as described in the above formula (1), as a specific example, the content described in any one of the above formulas (2) to (7) can be cited. q is an integer of 2 to 300.)
[0182] Next, the production method including the step (iii) will be described.
[0183] The production method comprises the steps of copolymerizing a silane coupling agent having a polymerizable double bond and a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group, and silane coupling the obtained polymer on a carrier surface.
[0184] Examples of the silane coupling agent having a polymerizable double bond include compounds having a structure represented by the following formula (VI).
[0185] [Chemical formula 16]
[0186] WXY-SiR 3-n Z n (VI)
[0187] (In formula (VI), W is a vinyl group, an allyl group, an isopropenyl group, or an alkenyl group having 4 to 12 carbon atoms and having a double bond at the ω position, X is an amide group, an ester group, an N-alkylamide group having 1 to 3 carbon atoms, an ether group, a sulfoxide group, a sulfone group, or a phosphate group, R is each independently an alkyl group having 1 to 5 carbon atoms, Z is a leaving group capable of forming a bond between the silicon atom in formula (VI) and the support, and Y is an alkylene group having 1 to 30 carbon atoms. n is an integer from 1 to 3.)
[0188] In the above formula (VI), Y is preferably an alkylene group having 1 to 5 carbon atoms, and more preferably any one of a methylene group, an ethylene group, and a propylene group.
[0189] R is preferably methyl or ethyl.
[0190] Z is a leaving group, and when the carrier is, for example, silica gel, it may be any atomic group as long as it is a group that can form a bond between the silicon atom in formula (VI) and the oxygen constituting the silica gel. Even when the carrier is not silica gel, it is a group that can form a bond between itself and the atoms constituting the carrier.
[0191] In order to achieve a good balance between ease of handling and reactivity, the group commonly used as the leaving group is an alkoxy group having 1 to 5 carbon atoms, among which methoxy and ethoxy can be exemplified. Halogen (chlorine, bromine or iodine), dimethylamino, diethylamino, pyrrolidinyl, nitrogen-containing groups such as imidazolyl, and allyl and isopropenyl can also be used. The reaction conditions (including the addition of a catalyst) can be adjusted according to the type of the leaving group.
[0192] Even in the production method including the above step (iii), as for the carrier, in addition to silica gel, the same carrier as that used in the production method including the above step (i) or (ii) can be used, and as for the (meth)acrylic monomer having a hydrophilic group or the (meth)acrylamide monomer having a hydrophilic group, the same monomer as that in the production method including the step (i) or (ii) can be used.
[0193] As the conditions for copolymerization, free radical copolymerization can be cited, and a small amount of free radical generator can be used as a catalyst to cause copolymerization. Regarding the free radical generator, the same substance as the free radical generator used in the manufacturing method of (i) can be used. In this manufacturing method, the molecular weight can also be controlled by using a suitable chain transfer agent or the above-mentioned living free radical polymerization method during polymer synthesis. Regarding the method for bonding the obtained polymer to the carrier by a silane coupling reaction, a known silane coupling method can be used.
[0194] It is estimated that the stationary phase according to one embodiment of the present invention obtained by the production method including the above step (iii) has the structure represented by the above (II).
[0195] Next, the production method including the step (iv) will be described.
[0196] The production method includes the step of copolymerizing a silane coupling agent having a polymerizable double bond and a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group in the presence of a carrier.
[0197] In this production method, the silane coupling agent having a polymerizable double bond can be the compound having a structure represented by formula (VI) used in the production method including the step (iii).
[0198] In addition, regarding the carrier, in addition to silica gel, the same carrier as that used in the production method including the above-mentioned step (i) or (ii) can also be used, and regarding the (meth)acrylic monomer having a hydrophilic group or the (meth)acrylamide monomer having a hydrophilic group, the same monomer as that used in the production method including the step (i) or (ii) can also be used.
[0199] The copolymerization conditions include free radical copolymerization, and a small amount of a free radical generator can be used as a catalyst to induce the copolymerization. The free radical generator can be a known free radical generator used in polymerization reactions, and specific examples thereof include azo compounds and peroxides.
[0200] It is estimated that the stationary phase according to one embodiment of the present invention obtained by the production method including the step (iv) has the structure represented by the above (II).
[0201] Next, a production method including step (v) is described. The production method is a production method including the steps of introducing a chain transfer functional group on the surface of a carrier and subjecting a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group to free radical polymerization. It should be noted that the chain transfer functional group may be the same functional group as the chain transfer functional group exemplified in the description of formula (III), and the same chain transfer functional group may also be cited as a preferred example.
[0202] In this production method, when silica gel is used as a support, the support to which the chain transfer functional group is bonded can be obtained by silane coupling the compound having a structure represented by formula (III) used in the production method including the above step (ii) with silica gel.
[0203] In the presence of a carrier having a chain transfer functional group introduced (chemically bonded) to the surface, a small amount of a free radical initiator is used as a catalyst to carry out free radical polymerization of a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group, thereby fixing the polymer on the carrier surface. As for the carrier, in addition to silica gel, the same carrier as that used in the production method including the above-mentioned step (i) or (ii) can be used, and as for the (meth) acrylic monomer having a hydrophilic group or the (meth) acrylamide monomer having a hydrophilic group, the same monomer as that used in the production method including the step (i) or (ii) can be used. In addition, as for the free radical generator, the same free radical generator as that used in the production method including the step (i) or (ii) can be used.
[0204] It is estimated that the stationary phase according to one embodiment of the present invention obtained by the production method including the step (v) has a structure represented by the above formula (v).
[0205] The stationary phase obtained by the production method including any of the steps (i) to (v) above also has excellent performance as a stationary phase for supercritical fluid chromatography.
[0206] The weight average molecular weight of the polymer having a hydrophilic group in the repeating unit of the main chain and bonded to the carrier of the stationary phase according to one embodiment of the present invention obtained through the above operation is preferably 1000 or more and 5000000 or less. It should be noted that the weight average molecular weight of the polymer referred to in the present invention is, for example, the repeating unit of the main chain in the case of the structure represented by the above formula (II) and (IV), i.e., -(CH2-CAB) n -The weight average molecular weight of the part.
[0207] The weight average molecular weight is preferably within the above range from the viewpoints of solubility of the polymer in the solvent, preventing aggregation of particles when the polymer is supported on a carrier, inhibiting dissolution in the mobile phase solvent, maintaining the bonding amount when chemically bonded to the carrier, etc. The optimal point varies depending on the type of polymer.
[0208] In the production method including steps (i), (iv), and (v), since polymerization of the monomer having a hydrophilic group and fixation to the silica gel occur simultaneously, the weight average molecular weight is estimated from the supernatant of the polymerization solution.
[0209] In the production method including steps (ii) and (iii), before the polymer having a hydrophilic group in a repeating unit of the main chain is bonded to the carrier, the weight average molecular weight of the polymer is measured.
[0210] The weight average molecular weight can be measured by a gel permeation chromatography (GPC) method using polystyrene, poly(methyl methacrylate) or poly(ethylene glycol) as standard substances.
[0211] In the stationary phase involved in one embodiment of the present invention, a polymer having a hydrophilic group in the repeating unit of the main chain is covalently bonded to the surface of the carrier. Therefore, even if a solvent that can originally dissolve these polymers or a mixed solvent containing the solvent is used as a developing solvent, dissolution will not occur and the function as a stationary phase will not be impaired.
[0212] The specific surface area of the stationary phase involved in one embodiment of the present invention is equivalent to the specific surface area of the carrier used, so a carrier of a desired specific surface area can be selected. In the case where the carrier is a porous inorganic particle including porous silica gel as an option, it can be adjusted by selecting an appropriate product. Generally speaking, in the method of supporting a polymer on a carrier, the specific surface area does not change by more than an error before and after the support, so the specific surface area of the stationary phase can be regarded as the same as the specific surface area of the carrier used.
[0213] When core-shell type particles are used as the carrier, the specific surface area thereof corresponds to the specific surface area of the shell.
[0214] The average particle size of the carrier that can be used in the present invention is usually 0.1 μm or more and 50 μm or less, in another embodiment, 1 μm or more and 40 μm or less, in another embodiment, 1 μm or more and 30 μm or less, in another embodiment, 1 μm or more and 5 μm or less, and in another embodiment, 1 μm or more and 3 μm or less. The average pore size is usually above, Below, in another way is above, In yet another embodiment, above, the following.
[0215] In the case of porous inorganic particles containing porous silica gel as an option, the specific surface area of the carrier is generally 5 m 2 / g or more, 1000m 2 / g or less, and 10m in another method 2 / g or more, 500m 2 On the other hand, in the case of nonporous inorganic particles including nonporous silica gel as an option, the specific surface area is usually less than 5 m 2 / g, in another way it is 4m 2 / g or less, usually 0.01m 2 / g or more. Generally speaking, if the polymer is supported on a carrier, the specific surface area does not change more than the error before and after the support, so the average particle size of the stationary phase can be regarded as the same as the average particle size of the carrier used. That is, the particle-shaped stationary phase of the present invention can be cited as having an average particle size of 0.1 μm or more and 1000 μm or less, usually 0.1 μm or more and 50 μm or less, and in another embodiment 1 μm or less and 50 μm or less.
[0216] The average thickness of the polymer supported on the carrier (supported amount per g of the carrier / carrier specific surface area) is preferably 0.5 nm or more and 5 nm or less. If it is within the above range, the peak tends to become sharp, which is preferred.
[0217] On the other hand, in the embodiment of the present invention, as a carrier, a core-shell particle having a non-porous core and a porous shell outside thereof can be used. In this specification, the core-shell particle is classified as a porous inorganic particle. The average pore diameter of the shell of the core-shell particle can be used as a particle of 9 nm or more, and in addition, a particle of 30 nm or more can also be used. The average pore diameter of the shell is usually less than 300 nm.
[0218] When the average pore diameter of the core-shell particle shell is 9 nm or more, and in another embodiment, 30 nm or more, it is expected that the substance serving as the ligand will penetrate into the shell of the core-shell particle and contribute to good separation of the target substance.
[0219] The average pore diameter of the shell of the core-shell particle can be measured by a gas adsorption method. The gas adsorption method is a method in which a gas is adsorbed on a porous sample while changing the pressure, the adsorption amount at this time is measured, the relative pressure (= the ratio of the pressure in the adsorption equilibrium state to the saturated vapor pressure) and the adsorption amount are plotted, and the specific surface area, pore volume, pore distribution, etc. are calculated using the adsorption-desorption isotherm obtained thereby. JIS Z8831-2 (mesopores and macropores) or JIS Z8831-3 (micropores) specified for the pore size distribution and pore characteristics of powders (solids) can be applied.
[0220] Here, the non-porosity mentioned in the present invention refers to the specific surface area (m 2 / g) is set as A, and the surface area (4πr calculated from the particle radius r) which can be obtained by using the particle diameter of the core particle 2 ) calculated surface area per unit weight (m 2 When (AB) / B×100 is less than 20,
[0221] On the other hand, the porosity mentioned in the present invention refers to the specific surface area of the surface measured by the BET method of 10 mm2 / g or above.
[0222] The ratio of the core to shell thickness of the core-shell particles is usually 1:9 to 9:1. From the viewpoint of ensuring good separation characteristics of the target substance, the ratio is preferably 4:1 to 2:1. The ratio can be adjusted by adjusting the thickness of the shell layer of the core-shell particles as described below.
[0223] Here, the thickness of the core refers to the diameter of the core.
[0224] The material constituting the core of the core-shell type particles is an inorganic substance. Specific examples thereof include inorganic substances selected from glass, metals such as titanium and zirconium or their metal oxides, and clay minerals such as bentonite and mica. Non-porous particles are preferred.
[0225] The core-shell particles used have an average particle size of usually 0.1 μm or more and 10 μm or less, preferably 1 μm to 5 μm, and more preferably 1 μm to 3 μm. It should be noted that the particle size of the core-shell particles mentioned in the present invention refers to the particle size measured by the average particle size measurement method based on the centrifugal sedimentation method.
[0226] The material constituting the shell of the core-shell type particles is a material obtained by further hydrolyzing a polyalkoxysiloxane obtained by partial hydrolysis of an alkoxysilane. Such a material is preferred from the viewpoint of being able to easily produce the core-shell type particles.
[0227] As the alkoxysilane, tetraalkoxysilane is preferred, and among them, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane are preferably used, and tetraethoxysilane is more preferably used.
[0228] When making the above-mentioned core-shell particles, reference can be made to Japanese Patent Publication No. 49-36396. Specifically, first, alkoxysilane is partially hydrolyzed to generate polyalkoxysiloxane. Then, the polyalkoxysiloxane thus obtained is dissolved in a solvent such as ether, acetone, dichloromethane, etc., thereby preparing a solution of polyalkoxysiloxane. The solution is applied to the above-mentioned particles that become the core or the above-mentioned core particles are immersed in the solution, and then the solvent is removed, so that the polyalkoxysiloxane is stacked on the surface of the core particles as a shell. And, afterwards, for the stacked polyalkoxysiloxane, it is subjected to polycondensation (hydrolysis) in the presence of water. Thus, core-shell particles can be obtained.
[0229] The thickness of the shell constituting the core-shell type particles can be appropriately adjusted within the range of 0.1 to 100 μm. The method for adjusting the thickness of the alkoxysilane constituting the shell can be exemplified by adjusting the viscosity of the alkoxysilane constituting the shell. For example, when increasing the thickness of the shell, the viscosity of the alkoxysilane can be reduced.
[0230] The specific surface area and pore diameter of the shell can be adjusted by laminating the shells and adjusting the pH of the aqueous solution used for polycondensation. For example, increasing the pH may be considered to increase the specific surface area and pore diameter.
[0231] Here, the thickness of the shell refers to a value obtained by subtracting the diameter of the core from the diameter of the core-shell type particle and dividing the resulting value by 2.
[0232] The core-shell type particles can use "core-shell silica gel" sold as a commercial product. Such commercial products are commercial products having pore diameters, specific surface areas, and particle sizes within the above ranges as catalog values. In addition, among such commercially available core-shell silica gels, core-shell silica gels in which the core is formed of glass and the shell is formed of silica gel (hydrolyzate of polyalkoxysiloxane) can be used.
[0233] The core-shell particles may be "core-shell silica gel" sold as a commercial product. Such commercial products have pore diameters, specific surface areas, and particle sizes within the above ranges as catalog values.
[0234] In the stationary phase obtained by supporting the polymer on the carrier, the mass fraction (%) of the polymer contained in 100 mass parts of the stationary phase is preferably 1 to 50 mass%, more preferably 3 to 30 mass%, and further preferably 5 to 30 mass%. By setting such a ratio, the adsorption capacity of the polymer can be appropriately expressed, and the situation of uselessly enhancing retention and the situation of broadening the peak can be avoided, so it is preferred.
[0235] It should be noted that the mass ratio (%) of the polymer contained in 100 parts by mass of the stationary phase can be measured by elemental analysis. Based on the carbon content of the support before the polymer is bonded, and the measurement results of the carbon content of the obtained stationary phase, all carbon other than the carbon contained in the support before the polymer is bonded is regarded as carbon derived from the polymer, thereby calculating the mass ratio of the polymer in the stationary phase.
[0236] The average particle size of the particulate stationary phase of the present invention refers to the diameter of a sphere if it is spherical, and the diameter of a sphere having the same volume as the particle if it is amorphous. The average particle size can be measured using a device that uses a microscope image, such as the Mastersizer 2000E manufactured by Malvern.
[0237] The particulate stationary phase of the present invention is preferably a spherical particle with an aspect ratio of 2 or less, preferably 1.5 or less. The closer to a sphere, the better, so the lower limit is 1, and there is no particular limitation.
[0238] The aspect ratio is measured as described below. The sample is randomly scattered on the observation table and observed from directly above using an electron microscope or an optical microscope. In any picture where more than 10 independent (not in contact with or repeated with any other particles) primary particles are observed, the major axis and the minor axis (the length of the longest part perpendicular to the major axis) are obtained for each independent primary particle in the picture, and the ratio of the two is used as the aspect ratio of each particle. The aspect ratios for all independent primary particles in the picture are arithmetic averaged, and the value obtained is used as the aspect ratio of the present invention. Primary particles refer to particles in which the interface between particles can be clearly observed. Usually, for observation, the primary particles are appropriately dispersed to avoid overlapping of the primary particles on the sample table, but it is difficult to avoid occasional overlap. In addition, there are block particles formed by the agglomeration of multiple primary particles, and these particles are excluded from the observation object.
[0239] The stationary phase according to one embodiment of the present invention is preferably used as a stationary phase for supercritical fluid chromatography (SFC).
[0240] When the stationary phase according to one embodiment of the present invention is used for SFC, it has excellent separation characteristics for hydrophilic substances.
[0241] The stationary phase according to one embodiment of the present invention can be used by being packed in a supercritical fluid chromatography column such as that described in Japanese Patent Application Laid-Open No. 2006-058147.
[0242] In supercritical fluid chromatography, a fluid containing a supercritical fluid and a solvent is used as a mobile phase. The supercritical fluid chromatography mentioned here is a general name for a chromatography with a supercritical fluid as the main mobile phase. The above-mentioned supercritical fluid is a substance in a state (i.e., a supercritical state) above the critical pressure and above the critical temperature. As a substance used as a supercritical fluid, for example, carbon dioxide, ammonia, sulfur dioxide, hydrogen halides, nitrous oxide, hydrogen sulfide, methane, ethane, propane, butane, ethylene, propylene, halogenated hydrocarbons, water, etc. can be cited. From the perspective of appropriate critical conditions, safety, cost, etc., it essentially refers to carbon dioxide. In addition, strictly speaking, supercriticality is not necessary, and the use under the subcritical state is also included in the interior and is called "supercritical fluid chromatography".
[0243] As the above-mentioned solvent, one or more than one solvent can be selected from various known solvents according to the type of the above-mentioned target substance, the type of supercritical fluid, etc. As the above-mentioned solvent, for example, lower alcohols such as methanol, ethanol, and 2-propanol, ketones such as acetone, acetonitrile, ethyl acetate, THF, etc. can be cited.
[0244] The supercritical fluid chromatograph is not particularly limited as long as it is a chromatograph using a fluid containing the supercritical fluid and the solvent as a mobile phase. The supercritical fluid chromatograph using the stationary phase according to one embodiment of the present invention can be used for analysis or fractionation.
[0245] The supercritical fluid chromatograph used for fractionation is not particularly limited as long as it includes the step of fractionating the mobile phase after passing through the column using a fraction collector according to the target substance separated in the column.
[0246] As the column to be packed, a column of known size can be used.
[0247] The flow rate may be appropriately adjusted for use, and an example thereof may be 0.3 to 10 mL / min, and a preferred example may be 1 to 6 mL / min.
[0248] In addition, the column temperature may be about 0 to 50°C, and may be about 20 to 40°C.
[0249] The back pressure may be about 120 to 180 bar, and may be about 130 to 160 bar.
[0250] The stationary phase for supercritical fluid chromatography of the present invention has excellent separation performance for hydrophilic substances such as water-soluble vitamins, amino acids, sugars, nucleic acids, and hydrophilic metabolites.
[0251] Example
[0252] Hereinafter, the present invention will be specifically described with reference to Examples. However, the present invention is not limited to the following Examples.
[0253] <Preparation Example 1>
[0254] (N-methyl-N-[3-(trimethoxysilyl)propyl]2-acrylamide treatment of silica gel)
[0255] First, the following steps were used to prepare a silane coupling agent containing acrylamide. 151 mg of 4-pyrrolidinopyridine was added to a flask, and nitrogen was purged after degassing. 95 mL of toluene, 4.04 mL of N-methylaminopropyltrimethoxysilane, and 5.66 mL of triethylamine were added thereto in sequence under a nitrogen atmosphere. Thereafter, 2.16 mL of a toluene solution (5 mL) of acryloyl chloride was added dropwise under a nitrogen atmosphere for about 10 minutes. The crude product of N-methyl-N-[3-(trimethoxysilyl)propyl]2-acrylamide was synthesized by heating at 60°C for 3 hours.
[0256] The crude product obtained by the above reaction is filtered, the triethylamine hydrochloride of the by-product is removed, and the filtrate is placed on 20.1g of silica gel. It should be noted that the silica gel is pre-dried in vacuum at 160°C for 3 hours and then cooled to room temperature. After the crude product is washed with about 10mL of toluene, the toluene solution dispersed with silica gel is heated to reflux at 130°C for 3 hours in an oil bath. After the heat treatment is completed, it is cooled to room temperature and filtered for recovery, and then washed with 100mL of toluene, 400mL of methanol and 200mL of acetone. The obtained stationary phase is vacuum dried at 60°C overnight to obtain silica gel bonded with acrylamide (hereinafter referred to as acrylamide-treated silica gel).
[0257] The carbon content of the silica gel thus obtained was 4.26% by mass. The specific surface area of the silica gel obtained was measured by the BET method and the result was 119 m 2 / g, and the average particle size was considered to be 3 μm.
[0258] <Example 1>
[0259] 1.11 g of 2-methacryloyloxyethyl phosphorylcholine (PA) was added to the flask, followed by 5.89 mL of 2-propanol and 0.1 mL of pyridine. 0.4 mL of a 0.23 M 2,2'-azobis(2-methylpropionic acid) dimethyl ester 2-propanol solution was added. Finally, 2.00 g of acrylamide-treated silica gel (average particle size 3 μm, average pore size 2.00 μm) obtained in Preparation Example 1 was added to the flask. ), the flask was heated to 60°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, the obtained powder was filtered and recovered, and then washed 4 times with 50 mL of methanol. The obtained stationary phase was vacuum dried at 60°C overnight.
[0260] The carbon content of the obtained silica gel was 8.81% by mass, while the carbon content of the raw silica gel was 4.26% by mass, from which it was estimated that about 12.7% by mass of poly(PA) was bonded. The carbon content was determined by elemental analysis, and the increase was calculated as the amount derived from poly(PA).
[0261] It can be estimated that the obtained poly(PA) bonded silica gel has the following structure.
[0262] [Chemical formula 17]
[0263]
[0264] <Example 2>
[0265] 1.69 g of 2-(N-3-sulfopropyl-N,N-dimethylammonium)ethyl methacrylate (AS) was added to the flask, followed by 5.23 mL of water and 0.1 mL of pyridine. 0.4 mL of an aqueous solution of 2,2'-azobis(2-methylpropionamidine) dihydrochloride adjusted to 0.38 M was added. Finally, 2.00 g of acrylamide-treated silica gel (average particle size of 3 μm, average pore size of 1.3 μm) obtained in Preparation Example 1 was added to the flask. ), the flask was heated to 70°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 10 mL of saturated brine was added to the obtained powder and filtered for recovery. Thereafter, the powder was washed twice with 10 mL of saturated brine, once with 50 mL of water, twice with 50 mL of methanol, and once with 50 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0266] The carbon content of the obtained silica gel was 10.02% by mass, while the carbon content of the raw silica gel was 4.19% by mass, from which it was estimated that about 15.6% by mass of poly(AS) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(AS).
[0267] It is estimated that the obtained poly(AS) bonded silica gel has the following structure.
[0268] [Chemical formula 18]
[0269]
[0270] <Example 3>
[0271] 1.83 g of 3-(methacryloylamino)propyltrimethylammonium chloride (A) was added to the flask, followed by 5.93 mL of 2-methoxyethanol and 0.1 mL of N,N-dimethylacetamide. 0.4 mL of 2-methoxyethanol solution of 2,2'-azobis(2-methylpropionic acid) dimethyl ester adjusted to 0.52 M was added thereto. Finally, 2.21 g of acrylamide-treated silica gel (average particle size 3 μm, average pore size 2.0 μm) obtained in Preparation Example 1 was added to the flask. ), the flask was heated to 80°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 10 mL of methanol was added to the obtained powder and filtered for recovery. Thereafter, it was washed 4 times with 50 mL of methanol and once with 50 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0272] The carbon content of the obtained silica gel was 10.09% by mass, while the carbon content of the raw silica gel was 4.19% by mass, from which it was estimated that about 13.3% by mass of poly(A) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(A).
[0273] It is estimated that the obtained poly (A) bonded silica gel has the following structure.
[0274] [Chemical formula 19]
[0275]
[0276] <Example 4>
[0277] 1.88 g of poly(ethylene glycol) monomethyl ether methacrylate (PEG) with a number average molecular weight of 500 was added to the flask, and 5.26 mL of diethylene glycol dimethyl ether and 0.1 mL of N,N-dimethylacetamide were added in sequence. 0.4 mL of diethylene glycol dimethyl ether solution adjusted to 0.234 M of 2,2'-azobis(2-methylpropionic acid) dimethyl ester was added thereto. Finally, 2.03 g of acrylamide-treated silica gel (average particle size of 3 μm and average pore size of 1.3 μm) obtained in Preparation Example 1 was added to the flask. ), the flask was heated to 80°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 10 mL of methanol was added to the obtained powder and filtered for recovery. Thereafter, it was washed 3 times with 50 mL of methanol and once with 50 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0278] The carbon content of the obtained silica gel was 12.24% by mass, while the carbon content of the raw silica gel was 4.19% by mass, from which it was estimated that about 18.6% by mass of poly(PEG) was bonded. The carbon content was determined by elemental analysis, and the increase was calculated as the amount derived from poly(PEG).
[0279] It can be inferred that the obtained poly(PEG) bonded silica gel has the following structure.
[0280] [Chemical formula 20]
[0281]
[0282] <Example 5>
[0283] 1.60 g of potassium 3-(methacryloyloxy)propanesulfonate (S) was added to the flask, followed by 5.81 mL of water and 0.1 mL of N,N-dimethylacetamide. 0.4 mL of an aqueous solution of 2,2'-azobis(2-methylpropionamidine) dihydrochloride adjusted to 0.38 M was added. Finally, 2.03 g of acrylamide-treated silica gel (average particle size 3 μm, average pore size 2.0 μm) obtained in Preparation Example 1 was added to the flask. ), the flask was heated to 80°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 10 mL of water was added to the obtained powder and filtered for recovery. Thereafter, it was washed twice with 10 mL of water, once with 40 mL of methanol, and once with 50 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0284] The carbon content of the obtained silica gel was 9.52% by mass, while the carbon content of the raw silica gel was 4.19% by mass, from which it was estimated that about 21.7% by mass of poly(S) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(S).
[0285] It is estimated that the obtained poly(S) bonded silica gel has the following structure.
[0286] [Chemical formula 21]
[0287]
[0288] <Example 6>
[0289] 0.98 g of 2-hydroxyethyl methacrylate (HEMA) was added to the flask, followed by 6.09 mL of 2-methoxyethanol and 0.1 mL of N,N-dimethylacetamide. 0.4 mL of 2-methoxyethanol solution of 2,2'-azobis(2-methylpropionic acid) dimethyl ester adjusted to 0.47 M was added thereto. Finally, 2.02 g of acrylamide-treated silica gel (average particle size of 3 μm, average pore size of ), the flask was heated to 80°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 10 mL of methanol was added to the obtained powder and filtered for recovery. Thereafter, it was washed 3 times with 50 mL of methanol and once with 50 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0290] The carbon content of the obtained silica gel was 10.45% by mass, while the carbon content of the raw silica gel was 4.19% by mass, from which it was estimated that about 13.9% by mass of poly(HEMA) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(HEMA).
[0291] It can be inferred that the obtained poly(HEMA) bonded silica gel has the following structure.
[0292] [Chemical formula 22]
[0293]
[0294] <Example 7>
[0295] 0.53 g of acrylamide (Am) was added to the flask, followed by 6.47 mL of water and 0.1 mL of N,N-dimethylacetamide. 0.4 mL of an aqueous solution of 2,2'-azobis(2-methylpropionamidine) dihydrochloride adjusted to 0.47 M was added. Finally, 2.21 g of acrylamide-treated silica gel (average particle size of 3 μm and average pore size of 1.3 μm) obtained in Preparation Example 1 was added to the flask. ), the flask was heated to 70°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 20 mL of methanol and 20 mL of water were added to the obtained powder, and then filtered and recovered. Thereafter, it was washed twice with 50 mL of water, once with 50 mL of methanol, and once with 50 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0296] The carbon content of the obtained silica gel was 7.87% by mass, while the carbon content of the raw silica gel was 4.19% by mass, from which it was estimated that about 8.6% by mass of poly(Am) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(Am).
[0297] It can be estimated that the obtained poly(Am) bonded silica gel has the following structure.
[0298] [Chemical formula 23]
[0299]
[0300] <Example 8>
[0301] 2.48 g of 2-methacryloyloxyethyl phosphorylcholine (PA) was added to the flask, followed by 8.92 mL of 2-methoxyethanol and 0.2 mL of N,N-dimethylacetamide. 0.4 mL of 2-methoxyethanol solution adjusted to 0.52 M of 2,2'-azobis(2-methylpropionic acid) dimethyl ester was added to the flask. Finally, 3.49 g of core-shell silica gel (average particle size of 2.7 μm, average pore size of 1.3 μm) treated with acrylamide obtained in the same manner as in Preparation Example 1 was added to the flask. The shell thickness was 0.5 μm), and the flask was heated to 80°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 10 mL of methanol was added to the obtained powder, and then filtered and recovered. Thereafter, it was washed 4 times with 50 mL of methanol. The obtained stationary phase was vacuum dried at 60°C overnight.
[0302] The carbon content of the obtained silica gel was 5.57% by mass, while the carbon content of the raw silica gel was 2.97% by mass, from which it was estimated that about 6.6% by mass of poly(PA) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(PA).
[0303] It can be inferred that the obtained poly(PA) bonded silica gel has the same structure as that of Example 1.
[0304] <Example 9>
[0305] 1.55 g of 2-methacryloyloxyethyl phosphorylcholine (PA) was added to the flask, followed by 5.45 mL of 2-methoxyethanol and 0.1 mL of N,N-dimethylacetamide. 0.4 mL of 2-methoxyethanol solution of 2,2'-azobis(2-methylpropionic acid) dimethyl ester adjusted to 0.33 M was added thereto. Finally, 2.24 g of silica gel (average particle size of 1.6 μm, average pore size of 1.6 μm) treated with acrylamide obtained in the same manner as in Preparation Example 1 was added to the flask. ), the flask was heated to 80°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 15 mL of methanol was added to the obtained powder and filtered for recovery. Thereafter, it was washed 4 times with 50 mL of methanol. The obtained stationary phase was vacuum dried at 60°C overnight.
[0306] The carbon content of the obtained silica gel was 14.02% by mass, while the carbon content of the raw silica gel was 6.49% by mass, from which it was estimated that about 24.5% by mass of poly(PA) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(PA).
[0307] It can be inferred that the obtained poly(PA) bonded silica gel has the same structure as that of Example 1.
[0308] <Example 10>
[0309] Add 3.55 g of 2-methacryloyloxyethyl phosphorylcholine (PA) to a flask, and add 12.5 mL of 2-methoxyethanol and 0.2 mL of N,N-dimethylacetamide in sequence. Add 0.8 mL of 2-methoxyethanol solution of 2,2'-azobis(2-methylpropionic acid) dimethyl ester adjusted to 0.37 M. Finally, add 5.01 g of non-porous silica gel (average particle size of 2.5 μm) treated with acrylamide obtained in the same manner as in Preparation Example 1 to the flask, heat the flask to 80°C in an oil bath and keep it for 6 hours. After the copolymerization is completed, add 20 mL of methanol to the obtained powder and filter and recover it. Thereafter, wash it 4 times with 50 mL of methanol. The obtained stationary phase is vacuum dried at 60°C overnight.
[0310] The carbon content of the obtained nonporous silica gel was 0.62% by mass, and the carbon content of the raw nonporous silica gel was 0.44% by mass, from which it was estimated that about 0.4% by mass of poly(PA) was bonded. The carbon content was determined by elemental analysis, and the increase was calculated as the amount derived from poly(PA).
[0311] It can be inferred that the obtained poly(PA) bonded silica gel has the same structure as that of Example 1.
[0312] <Example 11>
[0313] 1.55 g of 2-methacryloyloxyethyl phosphorylcholine (PA) was added to the flask, followed by 5.32 mL of 2-methoxyethanol and 0.1 mL of N,N-dimethylacetamide. 0.4 mL of a 0.33 M 2,2'-azobis(2-methylpropionic acid) dimethyl ester 2-propanol solution was added. 2.21 g of silica gel (average particle size 3 μm, average pore size ), and finally, 0.12 mL of 3-(trimethylsilyl)propyl methacrylate was added to the flask, and the flask was heated to 60°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 15 mL of methanol was added to the obtained powder, and then filtered and recovered. Thereafter, it was washed with 15 mL of methanol and 25 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0314] The carbon content of the obtained silica gel was 9.14% by mass, from which it was estimated that about 20.4% by mass of poly(PA) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(PA).
[0315] It can be inferred that the obtained poly(PA) bonded silica gel has the same structure as that of Example 1.
[0316] <Example 12>
[0317] 1.56 g of 2-methacryloyloxyethyl phosphorylcholine (PA) was added to the flask, followed by 5.45 mL of 2-methoxyethanol and 0.1 mL of N,N-dimethylacetamide. 0.4 mL of a 0.33 M solution of 2,2'-azobis(2-methylpropionic acid) dimethyl ester in 2-methoxyethanol was added. Finally, 2.21 g of acrylamide-treated silica gel (average particle size 3 μm, average pore size 2.3 μm) with thiol treatment on the surface was added to the flask. Commercially available), the flask was heated to 80°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 20 mL of methanol was added to the obtained powder and filtered for recovery. Thereafter, it was washed 3 times with 50 mL of methanol and once with 50 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0318] The carbon content of the obtained silica gel was 6.41% by mass, while the carbon content of the raw silica gel was 1.94% by mass, from which it was estimated that about 11.7% by mass of poly(PA) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(PA).
[0319] It can be estimated that the obtained poly(PA) bonded silica gel has the following structure.
[0320] [Chemical formula 24]
[0321]
[0322] <Example 13>
[0323] 1.68 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (AS) was added to the flask, followed by 5.33 mL of water and 0.1 mL of pyridine. 0.4 mL of an aqueous solution of 2,2'-azobis(2-methylpropionamidine) dihydrochloride adjusted to 0.38 M was added. Finally, 2.21 g of acrylamide-treated silica gel (average particle size 3 μm, average pore size 2.3 μm) with the surface treated with thiol was added to the flask. Commercially available), the flask was heated to 70°C in an oil bath and maintained for 6 hours. After the copolymerization was completed, 20 mL of saturated brine was added to the obtained powder and filtered for recovery. Thereafter, it was washed twice with 30 mL of saturated brine, twice with 30 mL of water, once with 50 mL of methanol, and once with 50 mL of acetone. The obtained stationary phase was vacuum dried at 60°C overnight.
[0324] The carbon content of the obtained silica gel was 2.35% by mass, while the carbon content of the raw silica gel was 1.94% by mass, from which it was estimated that about 0.9% by mass of poly(AS) was bonded. The carbon content was measured by elemental analysis, and the increase was calculated as the amount derived from poly(AS).
[0325] It is estimated that the obtained poly(AS) bonded silica gel has the following structure.
[0326] [Chemical formula 25]
[0327]
[0328] The poly (PA) bonded silica gel stationary phase obtained in Example 1 was filled into a 3.0 mmφ×150 mm column, and vitamin B1, vitamin B2, vitamin B6, and vitamin B12 were separated by SFC. Figure 1 This is the SFC chromatogram when the methanol containing 20mM ammonium formate as a modifier is changed from 10% to 60% under linear gradient conditions over 10 minutes. The flow rate is 3mL / min, the temperature is 40°C, and the back pressure is 15.0MPa. The detection conditions of the samples are as follows. Vitamin B1: UV 266nm, Vitamin B2: UV 268nm, Vitamin B6: UV 284nm, Vitamin B12: 361nm.
[0329] Figure 2 The existing commercially available P4VP column (DAICEL DCpak P4VP, particle size: 3 μm) was used in Figure 1 SFC chromatograms of water-soluble vitamins analyzed under the same conditions.
[0330] The stationary phase according to one embodiment of the present invention clearly exhibits good retention characteristics and separation capabilities for water-soluble vitamins.
[0331] The stationary phase slurry obtained in Examples 1 to 7 was filled in a 4.6 mmφ×150 mm column, and uridine was analyzed by HPLC using each column obtained. The analysis was performed under the conditions of flow rate: 1 mL / min, temperature: 25°C, mobile phase A: acetonitrile, mobile phase B: 20 mM ammonium acetate aqueous solution, and mobile phase ratio A:B=90:10. This sample is often used as an indicator of the retention strength of the stationary phase in the hydrophilic interaction chromatography (HILIC) mode (J. Chromatogr. A1218 (2011) 5903). The resulting chromatogram is shown in Figure 3 .
[0332] The analysis of uridine was performed using commercially available Agilent HILIC-Z columns (particle size: 2.7 μm), HILICON iHILIC Fusion (particle size: 3.5 μm), HILICON iHILIC Fusion (+) (particle size: 3.5 μm), HILICON iHILIC Fusion (P) (particle size: 5.0 μm), DAICEL, DCpak P4VP (particle size: 3.0 μm), Merck, ZIC-HILIC (particle size: 3.0 μm) columns under the same conditions as when the stationary phases of Examples 1 to 7 were used. The chromatograms are shown in FIG. Figure 4 Table 1 summarizes the Figure 3 , 4 The retention coefficient (k) value shown in the chromatogram of . The retention time of toluene is set as t0 for calculation. It can be seen that: in particular, in Examples 3 and 5, better retention characteristics are shown than those of existing commercial products.
[0333] [Table 1]
[0334] Table 1
[0335]
[0336] The stationary phase slurry obtained in Example 8 was filled in a 3.0 mm φ × 50 mm column, and uridine was analyzed by HPLC using the obtained column. The analysis was performed under the conditions of flow rate: 0.43 mL / min, temperature: 25°C, mobile phase A: acetonitrile, mobile phase B: 20 mM ammonium acetate aqueous solution, mobile phase ratio A: B = 90:10. The resulting chromatogram is shown in Figure 5 Although the solution was passed at a low flow rate, the retention time was shorter than that in Example 1 and the peak symmetry was good, so it can be said that it is suitable for high-throughput analysis.
[0337] The stationary phase slurry obtained in Examples 1, 9, 11, and 12 was filled into a 4.6 mm φ × 150 mm column, and uridine was analyzed by HPLC using each column obtained. The analysis was performed under the conditions of flow rate: 1 mL / min, temperature: 25°C, mobile phase A: acetonitrile, mobile phase B: 20 mM ammonium acetate aqueous solution, and mobile phase ratio A: B = 90:10. The resulting chromatogram is shown in Figure 6 Compared with Example 1, Examples 9 and 12 give sharp peaks. Table 1 summarizes Figure 6 The retention coefficient (k) value shown in the chromatogram.
[0338] Industrial Applicability
[0339] The stationary phase involved in one embodiment of the present invention has good separation characteristics for substances that are difficult to separate using conventional separation agents, particularly hydrophilic substances. Specifically, an increase in the number of plates of the column can be expected. In addition, it is also shown that the retention characteristics of hydrophilic compounds are better than existing commercial products. It can be expected that the stationary phase involved in one embodiment of the present invention not only helps to discover or improve new separation conditions for various substances that have been difficult to separate so far, but also helps to improve the convenience of identification and analysis of the separated substances.
Claims
1. A stationary phase for chromatography, comprising inorganic carrier particles to which a polymer having a hydrophilic group in a repeating unit of the main chain is bonded, The stationary phase has a structure represented by the following formula (II): [Chemical formula 1] In formula (II), W' is a single bond or an alkylene group having 1 to 10 carbon atoms which may be branched, W" is hydrogen or an alkyl group having 1 to 12 carbon atoms, X is an amide group, an ester group, an N-alkylamide group having 1 to 3 carbon atoms, an ether group, a sulfoxide group, a sulfone group, a thioether group or a phosphate group, Y is an alkylene group having 1 to 30 carbon atoms, V is an ether group bonded to the surface of an inorganic support, an alkoxy group having 1 to 5 carbon atoms, a halogen, an alkylthiol group having 1 to 20 carbon atoms, a nitrogen-containing group, an allyl group, a 2-methyl-2-propenyl group or an alkyl group having 1 to 3 carbon atoms, and R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms, R 2 is an alkylene group having 1 to 12 carbon atoms, R 3 is a single bond, X 2 For -O-, Y 2 is a single bond or (-(CH2) a -O-) b , a is an integer of 1 to 5, b is an integer of 1 to 20, Z 2 is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, -N + R 4 3. -SO3 - 、-CO2 - or-PO4-R 4 , R 4 It is hydrogen, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms; p is 1 to 10, and q is 10 to 3000.
2. A stationary phase for chromatography, which is composed of inorganic carrier particles to which a polymer having a hydrophilic group in a repeating unit of the main chain is bonded, The stationary phase has a structure represented by the following formula (V), [Chemical formula 2] In formula (V), Y is a single bond or an alkylene group having 1 to 30 carbon atoms, V is an ether group bonded to the surface of the inorganic support, an alkoxy group having 1 to 5 carbon atoms, a halogen, a nitrogen-containing group, an allyl group, an isopropenyl group, or an alkyl group having 1 to 5 carbon atoms, T' is an alkylene residue having 1 to 12 carbon atoms or a thioether group, and R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms, R 2 is an alkylene group having 1 to 12 carbon atoms, R 3 is a single bond, X 2 For -O-, Y 2 is a single bond or (-(CH2) a -O-) b , a is an integer of 1 to 5, b is an integer of 1 to 20, Z 2 is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, -N + R 4 3. -SO3 - 、-CO2 - or-PO4-R 4 , R 4 is hydrogen, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms; and q is an integer of 2 to 300.
3. A stationary phase for chromatography, which is composed of inorganic carrier particles to which a polymer having a hydrophilic group in a repeating unit of the main chain is bonded, The stationary phase has a structure represented by the following formula (II): [Chemical formula 3] In formula (II), W' is a single bond or an alkylene group having 1 to 10 carbon atoms which may be branched, W" is hydrogen or an alkyl group having 1 to 12 carbon atoms, X is an amide group, an ester group, an N-alkylamide group having 1 to 3 carbon atoms, an ether group, a sulfoxide group, a sulfone group, a thioether group or a phosphate group, Y is an alkylene group having 1 to 30 carbon atoms, V is an ether group bonded to the surface of an inorganic support, an alkoxy group having 1 to 5 carbon atoms, a halogen, an alkylthiol group having 1 to 20 carbon atoms, a nitrogen-containing group, an allyl group, a 2-methyl-2-propenyl group or an alkyl group having 1 to 3 carbon atoms, and R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms, R 2 is a single bond, R 3 is a single bond, X 2 is -NH- or -N(CH3)-, Y 2 is a single bond, Z 2 It is hydrogen or an alkyl group having 1 to 6 carbon atoms; p is 1 to 10, and q is 10 to 3000.
4. A stationary phase for chromatography, which is composed of inorganic carrier particles to which a polymer having a hydrophilic group in a repeating unit of the main chain is bonded, The stationary phase has a structure represented by the following formula (V), [Chemical formula 4] In formula (V), Y is a single bond or an alkylene group having 1 to 30 carbon atoms, V is an ether group bonded to the surface of the inorganic support, an alkoxy group having 1 to 5 carbon atoms, a halogen, a nitrogen-containing group, an allyl group, an isopropenyl group, or an alkyl group having 1 to 5 carbon atoms, T' is an alkylene residue having 1 to 12 carbon atoms or a thioether group, and R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms, R 2 is a single bond, R 3 is a single bond, X 2 is -NH- or -N(CH3)-, Y 2 is a single bond, Z 2 is hydrogen or an alkyl group having 1 to 6 carbon atoms; q is an integer of 2 to 300.
5. The chromatographic stationary phase according to any one of claims 1 to 4, characterized in that The inorganic carrier particles are porous inorganic particles or non-porous inorganic particles.
6. The chromatographic stationary phase according to claim 5, wherein The inorganic carrier particles are porous inorganic particles, and the porous inorganic particles are core-shell type particles.
7. The chromatographic stationary phase according to any one of claims 1 to 4, characterized in that The average particle size is 0.1μm to 50μm.
8. The chromatographic stationary phase according to any one of claims 1 to 4, which is used for supercritical fluid chromatography.
9. A method for separating a target substance, comprising: A step of separating a target substance using the stationary phase according to any one of claims 1 to 8 and a mobile phase containing a supercritical fluid.
10. A method for producing a stationary phase for chromatography, comprising any of the following steps (i) to (v): (i) a step of subjecting a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group to free radical copolymerization with inorganic carrier particles to which a polymerizable functional group is bonded; (ii) a step of subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to free radical polymerization in the presence of a chain transfer agent having a crosslinkable silyl group at the end to obtain a polymer, and a step of subjecting the obtained polymer to silane coupling on the surface of inorganic carrier particles; (iii) a step of copolymerizing a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group with a silane coupling agent having a polymerizable double bond, and a step of silane coupling the obtained polymer on the surface of inorganic carrier particles; (iv) a step of copolymerizing a silane coupling agent having a polymerizable double bond and a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group in the presence of inorganic carrier particles; (v) a step of introducing a chain transfer functional group on the surface of the inorganic carrier particles to subject a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to free radical polymerization, in, The (meth)acrylic monomer having a hydrophilic group or the (meth)acrylamide monomer having a hydrophilic group in any of the steps (i) to (v) has a structure represented by the following formula (1): [Chemical formula 5] In formula (1), R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms, R 2 is an alkylene group having 1 to 12 carbon atoms, R 3 is a single bond, X 2 For -O-, Y 2 For a single key or a is an integer of 1 to 5, b is an integer of 1 to 20, Z 2 is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, -N + R 4 3. -CO2 - or R 4 It is hydrogen, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms.
11. A method for producing a stationary phase for chromatography, comprising any of the following steps (i) to (v): (i) a step of subjecting a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group to free radical copolymerization with inorganic carrier particles to which a polymerizable functional group is bonded; (ii) a step of subjecting a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to free radical polymerization in the presence of a chain transfer agent having a crosslinkable silyl group at the end to obtain a polymer, and a step of subjecting the obtained polymer to silane coupling on the surface of inorganic carrier particles; (iii) a step of copolymerizing a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group with a silane coupling agent having a polymerizable double bond, and a step of silane coupling the obtained polymer on the surface of inorganic carrier particles; (iv) a step of copolymerizing a silane coupling agent having a polymerizable double bond and a (meth) acrylic monomer having a hydrophilic group or a (meth) acrylamide monomer having a hydrophilic group in the presence of inorganic carrier particles; (v) a step of introducing a chain transfer functional group on the surface of the inorganic carrier particles to subject a (meth)acrylic monomer having a hydrophilic group or a (meth)acrylamide monomer having a hydrophilic group to free radical polymerization, in, The (meth)acrylic monomer having a hydrophilic group or the (meth)acrylamide monomer having a hydrophilic group in any of the steps (i) to (v) has a structure represented by the following formula (1): [Chemical formula 6] In formula (1), R 1 is hydrogen or an alkyl group having 1 to 6 carbon atoms, R 2 is a single key, R 3 is a single key, X 2 is -NH- or -N(CH3)-, Y 2 is a single key, Z 2 It is hydrogen or an alkyl group having 1 to 6 carbon atoms.
12. The method for producing a chromatographic stationary phase according to claim 10 or 11, characterized in that: The inorganic carrier particles are porous inorganic particles or non-porous inorganic particles.
13. The method for producing a chromatographic stationary phase according to claim 12, wherein: The inorganic carrier particles are porous inorganic particles, and the porous inorganic particles are core-shell type particles.
Citation Information
Patent Citations
JP1974036396A
Adsorption separating medium, packing material for chromatograph, column therefor, and liquid chromatography
JP2003337125A
Column for supercritical fluid chromatography
JP2006058147A
Monolithic silica column for separating biomicromolecule, method of manufacturing the same, and method of separating biomicromolecule
JP2010190602A